Proposta de uma sequência didática autoinstrucional sobre educação financeira para uso escolar ou cotidiano - Nicoleti, Valdir Roberto (2021)
The present work was developed in third-year (high school) classes in the E.E. “Writer Rachel de Queiroz ”in the city of Campinas / SP with a focus on Financial Education and Financial Mathematics, motivated by the large number of defaulting people in Brazil. In the work we present the economic situation during the pandemic period and analyze it under the bias of Financial Mathematics, of the products of the financial market and of the official documents that discipline and guide the teaching process of Basic Education. The research has a qualitative nature and the case study was used as a methodology. The structure of the proposed intervention and consolidation of a self-instructional material was presented in seven organizational sheets on Financial Education. The development of the proposal had a hybrid character, with initial guidance and filling out Form 1 in the classroom, and the rest with families. Finally, the proposal was validated through a final evaluation filled by electronic form.